Periodontal illness in diabetic patients of the educational policlinic "Julián Grimau". Santiago from Cuba. Cuba - Hechavarría Martínez, Bárbara Olaydis (2017)
Objetive: To identify the periodontal status of patients with Diabetes Mellitus. Methods: A descriptive and cross- sectional study was conducted in 125 adult patients of the medical clinic from the family No. 33, belonging to the Educational Policlinic "Julian Grimau", in the city of Santiago from Cuba, during one year. The Periodontal Index of Russell was used to determine the severity of the periodontal illness and the Index of quantitative analysis of Love to specify the degree of buccal hygiene. Results: The present research showed that most of the patients were female (92.5%), prevailing the established periodontitis for a (53.0%). Conclusions: In diabetic patients there is an increment on the severity of periodontal disease and the oral hygiene was deficient. It is recommended to generate educational interventions in diabetic patients to improve their oral hygiene.